Health Care Savings from Microbiological Caries Risk - Athanasios 1. Zavras, DMD, MSc, DrMSc; Burton L. Edelstein, DDS, MPH; Athanasios Vamvakidis, BS, PhD (Blackwell Synergy, 2000)
Modeling new biomedical technologies and determining their expected cost is necessary before initiating formal clinical trials. This paper estimates an economic model for the potential cost impact of microbiological screening of toddlers for caries risk compared to the traditional method of managing pediatric caries. Methods: Potential cost savings were calculated based on screening test properties (sensitivity and specificity) derived from a population of 1,180 children aged 1 to 3 years with a caries prevalence of 15 percent. An algorithm was then developed to allocate prevalent and anticipate incident caries, treatment effectiveness assumptions, and existing regional treatment costs.